2003
DOI: 10.1039/b300562n
|View full text |Cite
|
Sign up to set email alerts
|

Reaction between N2O and CH4 over Fe ion-exchanged BEA zeolite catalyst: A possible role of nascent oxygen transients from N2O

Abstract: The reaction between N 2 O and CH 4 over an Fe ion-exchanged BEA zeolite (Fe-BEA) catalyst was studied by using a pulse reaction technique, temperature-programmed desorption (TPD) and infrared (IR) spectroscopy. N 2 O readily reacted with CH 4 in the presence of an N 2 O + CH 4 mixture above 200 C, while both the O 2 + CH 4 reaction and the catalytic decomposition of N 2 O over the Fe-BEA catalyst required higher temperatures (above 400 C). In the O 2 -TPD studies, a desorption peak of O 2 was observed above 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
59
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 27 publications
14
59
0
1
Order By: Relevance
“…Chen et al [5] have reported that the hydroxyl group stretching over binuclear iron species in Fe-ZSM-5 prepared by sublimation method at 3665 cm )1 . Hydroxylated iron species are also observed by Mauvezin et al [31] and Kameoka et al [43] in Fe-BEA and by Wood et al [11] in Fe/ AlZSM-5. Wood et al [11] have attributed the observed IR bands at 3680 and 3628 cm )1 to symmetric and asymmetric stretching vibrations of isolated iron species having two hydroxl groups (-Fe(OH) 2 ).…”
Section: Drift Spectra Of No Adsorptionmentioning
confidence: 57%
“…Chen et al [5] have reported that the hydroxyl group stretching over binuclear iron species in Fe-ZSM-5 prepared by sublimation method at 3665 cm )1 . Hydroxylated iron species are also observed by Mauvezin et al [31] and Kameoka et al [43] in Fe-BEA and by Wood et al [11] in Fe/ AlZSM-5. Wood et al [11] have attributed the observed IR bands at 3680 and 3628 cm )1 to symmetric and asymmetric stretching vibrations of isolated iron species having two hydroxl groups (-Fe(OH) 2 ).…”
Section: Drift Spectra Of No Adsorptionmentioning
confidence: 57%
“…Low reaction orders of O2 are often observed for catalysts on which the loaded metal is easily oxidized or onto which O2 can easily adsorb. Taking into account the results of O2-TPD reported in the literature 29), 30) and the standard enthalpy change of formation of metal oxides, Fe species adsorb O2 more strongly and tend to be oxidized more easily than Cu species, suggesting a lower reaction order of O2 for the Fe/zeolite catalyst. However, the opposite phenomenon was observed in the present work.…”
Section: Inhibition Effect Of Nh3 On O2 Adsorptionmentioning
confidence: 99%
“…However, to our knowledge, recent studies about N 2 O-CH 4 SCR are mostly focused on Fe-Beta and Fe-MFI catalysts to understand the CH 4 activation mechanism in N 2 O-SCR [25][26][27][28], and there is no report about how SCR of N 2 O by CH 4 is affected by the co-existence NO, O 2 and/or H 2 O that are inevitably present in the N 2 O emission site, such as the nitric acid and adipic acid factories. Although most zeolite catalysts suffer the activity loss during the operation under these practical conditions, we have luckily found that Fe-USY zeolite shows a high activity and a high hydrothermal stability for N 2 O decomposition in our previous studies under the similar conditions [11,12].…”
Section: Introductionmentioning
confidence: 99%